2019
DOI: 10.3389/fmicb.2019.00895
|View full text |Cite
|
Sign up to set email alerts
|

Soil Abiotic Properties and Plant Functional Traits Mediate Associations Between Soil Microbial and Plant Communities During a Secondary Forest Succession on the Loess Plateau

Abstract: In the context of secondary forest succession, aboveground-belowground interactions are known to affect the dynamics and functional structure of plant communities. However, the links between soil microbial communities, soil abiotic properties, plant functional traits in the case of semi-arid and arid ecosystems, are unclear. In this study, we investigated the changes in soil microbial species diversity and community composition, and the corresponding effects of soil abiotic properties and plant functional trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 92 publications
(128 reference statements)
8
44
2
Order By: Relevance
“…In agreement to our results, long-lasting land-use effects on the soil fungal community composition were demonstrated even after 80 years of natural succession from farming and logging in tropical forests of Puerto Rico [68]. Furthermore, Chai et al [77] demonstrated that significant compositional differences of the fungal community between managed and recovering sites were only apparent after more than a decade of natural succession from farmland to secondary forest. No differences were found in early establishment phases up to 15 years after stopping management [77].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement to our results, long-lasting land-use effects on the soil fungal community composition were demonstrated even after 80 years of natural succession from farming and logging in tropical forests of Puerto Rico [68]. Furthermore, Chai et al [77] demonstrated that significant compositional differences of the fungal community between managed and recovering sites were only apparent after more than a decade of natural succession from farmland to secondary forest. No differences were found in early establishment phases up to 15 years after stopping management [77].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Chai et al [77] demonstrated that significant compositional differences of the fungal community between managed and recovering sites were only apparent after more than a decade of natural succession from farmland to secondary forest. No differences were found in early establishment phases up to 15 years after stopping management [77]. Agroforestry systems promote compositional shifts in the fungal community and abundance of mycorrhizal fungi compared to monocultures for a variety of tropical crops, including coffee [78], cacao [35], and rubber [28].…”
Section: Discussionmentioning
confidence: 99%
“…The distance between any two plots at the same stage was more than 1 km to include different community types and avoid spatial autocorrelation in variables and pseudo-replications (Conti and D ıaz 2013). The plot size was 20 9 20 m. Specifically, our previous survey and study (Chai et al 2019). S1-S6 represent 1-4, 4-8, 8-15, 15-50, 50-100, and 100-150 yr after abandonment, respectively. ensured that all the plots had the same agricultural history and are now on a similar trajectory toward climax forest under natural conditions (Chai et al 2015).…”
Section: Study Sitementioning
confidence: 99%
“…Distribution patterns and drivers of soil microbes have attracted extensive attention over the past several years. Previous studies have provided evidences that environmental heterogeneity could drive the composition and distribution of the microbial community (Maestre et al, 2015; Chai et al, 2019; Vieira et al, 2019; Zhang L. et al, 2019). For instance, Zhang K. et al (2019) confirmed that differences in salinity negatively correlated with the similarity of the microbial community in a desert ecosystem, and the composition of the bacterial community converged on salt-tolerant species with increasing habitat salinity (Rath et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have indicated that soil water content (WC; Zhang et al, 2013; Maestre et al, 2015) and soil texture (Hu et al, 2014) have also affected a shift in the microbial community composition. Plant attributes, including plant diversity and functional traits, may be another factor that regulates microbes directly by determining the quality and quantity of leaf litter and root exudates or indirectly by influencing soil physiochemical properties (Soussi et al, 2016; Chai et al, 2019). However, it is still unclear how soil properties and plant attributes simultaneously drive the local assemblage and distribution of microorganisms.…”
Section: Introductionmentioning
confidence: 99%